Salt diffusion effect on the submarine permafrost state and distribution as well as on the stability zone of methane hydrates on the Laptev Sea shelf - V. V. Malakhova; A. V. Eliseev (Лëд и снег, 2020)
Salt transport in shelf sediments can affect the state of the submarine permafrost and the thermodynamic stability of hydrates. To estimate the effect of salt transport, we used a model analysis of salinization of underwater sediments. It is assumed that the salininization follows the flooding of the shelf, which accompanies transgression of the ocean during the end of the glaciations of the Quaternary period. We used the model of thermal processes in the bottomset bed, developed in collaboration with the Institute of Numerical Mathematics and Mathematical Geophysics, Siberian Branch of the Russian Academy of Sciences and the A.M. Obukhov Institute of Atmospheric Physics, Russian Academy of Science. The model was augmented by the equation of salt diffusion in the bottom sediments. In calculations with the model, changes in the temperature of the upper surface of bottom sediments and sea level over the past 400 kyr were prescribed (set). It is shown that the combined effect of heat and salinization of bottom sediments during oceanic transgressions (shelf flooding) leads to the sinking of the current upper boundary of the marine permafrost by about 10–25 m below the sea floor, depending on the current depth of the shelf. Accounting for the salt diffusion is necessary to determine the position of the upper boundary of the permafrost, as well as to calculate the rate of its degradation. In particular, salt transport is able to change both the current position and the rate of displacement of the upper permafrost boundary in several times relative to the case of a time-independent freezing temperature. Note, that this effect is insignificant for estimation of the position of the lower permafrost boundary in the bottom sediments of the inner shelf. Lowering the freezing point leads to the fact that frozen rocks on the outer shelf completely thaw at negative temperatures of bottom sediments under the influence of heat and salts in the present period (experiments TF‑2, TFSAL2). The influence of salinity on the characteristics of the stability zone of methane hydrates in the submarine permafrost is insignificant due to deep level of their occurrence in the shelf sediments.